Burden of adult atopic dermatitis and unmet needs with existing therapies. (31st December 2023) - Bacci, Elizabeth D.; Correll, Julia R.; Pierce, Evangeline J.; Atwater, Amber Reck; Dawson, Zach; Begolka, Wendy Smith; Butler, Lisa
Abstract: Objective: Patients with atopic dermatitis (AD) have low treatment satisfaction. In this study, we evaluated the humanistic burden, treatment satisfaction, and treatment expectations in patients with AD in the United States. Methods: Adults with AD recruited through the National Eczema Association and clinical sites completed a web-based survey comprising the Patient-Oriented SCORing Atopic Dermatitis (PO-SCORAD), Dermatology Life Quality Index; Work Productivity and Activity Impairment Questionnaire-Atopic Dermatitis; Treatment Satisfaction Questionnaire for Medication (TSQM); and answered questions on healthcare provider (HCP) visits, treatment history, and treatment goals. Descriptive analyses were performed to compare participants by severity. Results: Among 186 participants (mean [standard deviation] age 39.7 [15.3] years, 79.6% female), 26.9%, 44.6%, and 26.3% of the participants had mild, moderate, or severe AD, respectively, based on PO-SCORAD. Greater disease severity was associated with a greater impact on work and daily life, decreased TSQM scores, and increased HCP visits. Corticosteroid topical cream or ointment (53.8%) and oral antihistamines (31.2%) were most commonly used for the treatment of AD. Participants reported declining/stopping/changing AD treatment due to the potential for side effects or lack of efficacy. 'Leading normal lives' (28.0%) and 'being itch-free' (33.9%) were important treatment goals. Conclusions: Individuals with AD, especially severe disease, face a considerable humanistic burden even while using treatment.